Utilizing digital picture series to enhance students’ performance in writing narrative text - Nichella Ayu Clarita; Ashadi Ashadi; Ulfa Amalia; Juhansar Juhansar (Universitas Islam Sultan Agung, 2023)
The contemporary educational environment requires teachers to embrace innovation and creativity to facilitate learning through the use of technology. Digital picture series, as a technology-based approach, can enhance students' writing skills in narrative texts. The purpose of this study is to explore the implementation of digital picture series in learning-teaching English and its impact on students' performance in writing narrative texts. Collaborative classroom action research was used in this study, with 30 respondents consisting of 19 females and 11 males. Data were collected through observation, interviews, and tests. Data were analyzed qualitatively and quantitatively using the Grammarly application. The findings indicate that the implementation of digital picture series was successful, and students' performance in writing narrative texts improved from 60.55 to 75.00. The implementation process followed a structured approach consisting of need analysis, planning, acting, observing, and reflecting in cycle I, followed by problem-solving and re-planning, action, observation, and reflection in cycle II. Researchers recommend further researchers evaluating the effectiveness of digital picture series and placing greater emphasis on writing components.